2012
DOI: 10.1177/1744629512456465
|View full text |Cite
|
Sign up to set email alerts
|

Examining the support needs of ageing family carers in developing future plans for a relative with an intellectual disability

Abstract: Findings of this study clearly identify the emotional, informational and practical supports required by these ageing family carers. These findings have national and international relevance in influencing how governments and service providers support parent and sibling carers to proactively plan for the future, and in the development of both in-home and out-of-home options when a family carer can no longer provide care. This is more urgent than ever given the growing numbers of older persons with intellectual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
1
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(174 citation statements)
references
References 39 publications
5
151
1
17
Order By: Relevance
“…Sibling fears for the future concerned a lack of appropriate services, increased care demands and health issues. The view that futures planning is stressful for older parents and siblings is clear within existing research (Mansell & Wilson 2010;Taggart et al 2012) with main barriers cited as insufficient information and a lack of confidence in service providers (Gilbert et al 2008;Arnold et al 2012). Only three participants referred to the future wishes of the person with an intellectual disability which could suggest that they are overlooked in the futures planning process, that siblings are unaware of their wishes or are not included in the process, the literature suggests that all three scenarios are likely (Bowey & McGlaughlin 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sibling fears for the future concerned a lack of appropriate services, increased care demands and health issues. The view that futures planning is stressful for older parents and siblings is clear within existing research (Mansell & Wilson 2010;Taggart et al 2012) with main barriers cited as insufficient information and a lack of confidence in service providers (Gilbert et al 2008;Arnold et al 2012). Only three participants referred to the future wishes of the person with an intellectual disability which could suggest that they are overlooked in the futures planning process, that siblings are unaware of their wishes or are not included in the process, the literature suggests that all three scenarios are likely (Bowey & McGlaughlin 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This expectation has been seen in some studies to have been present in childhood and adolescence, demonstrating anticipation of a future care role (Wilson 2011;Angell et al 2012). Futures planning is seen to be an area of difficulty within the literature (Mansell & Wilson 2010;Taggart et al 2012) and adult siblings have reported particular concern for the time when parents are no longer available to provide support (Benderix & Sivberg 2007;Orsmond & Seltzer 2007), and worry about financial, legal and care arrangements (Rawson 2009;Atkin & Tozer 2011). Regarding future expectations for co-residence, some brothers and sisters plan to co-reside with the disabled sibling, whereas others do not (Bigby 1996;Heller 2000).…”
Section: Introductionmentioning
confidence: 98%
“…This area has begun to be explored in research, yet with little resolution or answers to ease the worry of ageing parents of young people with intellectual disability [36,37]. Research has suggested that this time when the young adults transition to adulthood, has been referred to as 'the second shock' by parents, paralleling transition with the initial diagnosis [38].…”
Section: Family Levelmentioning
confidence: 99%
“…This highlights the magnitude of the impact this time has on parents. In another study carers have reported that they experience a range of health problems and that their caregiving role results in high levels of anxiety [37]. A recent review suggested there was going to be a 'new' population of older people with intellectual disability due to improved survival and there is an urgent need to develop services and support structures to assist these families [39] Some work has begun to identify alternatives for these often stressed and anxious families.…”
Section: Family Levelmentioning
confidence: 99%
“…Some participants seemed to feel that practitioners conveyed a sense that they felt inadequate or were unwilling to discuss these matters. Other studies have found similar expressions of concern among older parent carers of people with learning disabilities (Mansell and Wilson, 2010;Taggart et al, 2012). This may be a subject for peer or group discussion and supervision but also shared learning and skill development with others who work in areas of practice that encompass death and dying.…”
Section: Implications For Practicementioning
confidence: 80%